Imaging Technologies Build Capacity and Accessibility in Phytoplankton Species Identification Expertise for Research and Monitoring: Lessons Learned During the COVID-19 Pandemic - Clayton, Sophie; Gibala-Smith, Leah; Mogatas, Kathryn; Flores-Vargas, Chanel; Marciniak, Kayla; Wigginton, Maci; Mulholland, Margaret R. (Frontiers in Microbiology, 2022)
As primary producers, phytoplankton play an integral role in global biogeochemical cycles through their production of oxygen and fixation of carbon. They also provide significant ecosystem services, by supporting secondary production and fisheries. Phytoplankton biomass and diversity have been identified by the GOOS as Essential Ocean Variables, properties that need to be monitored to better understand and predict the ocean system. Phytoplankton identification and enumeration relies on the skills and expertise of highly trained taxonomic analysts. The training of new taxonomic analysts is intensive and requires months to years of supervised training before an analyst is able to independently and consistently apply identification skills. During the COVID-19 pandemic, access to laboratories was restricted and social distancing requirements prevented supervised training. However, access to phytoplankton imaging technologies such as the Imaging FlowCytobot, FlowCam, and PlanktoScope, combined with open online taxonomic identification platforms such as EcoTaxa, provided a means to continue monitoring, research, and training activities remotely. Although such technologies cannot entirely replace microscopy, they have potential for supporting an expansion in taxonomic training, monitoring, and research capacity. We highlight a set of imaging and collaboration tools and describe how they were leveraged during lockdowns to advance research and monitoring goals. Anecdotally, we found that the use of imaging tools accelerated the training of new taxonomic analysts in our laboratory. Based on these experiences, we outline how these technologies can be used to increase capacity in taxonomic training and expertise, and how they can be used more broadly to expand research.